Cyber Security Analysis for Quantum Computing - Bindhu, V. (Journal of ISMAC, 2022)
The next phase of the quantum revolution is the Quantum computer Network, a network that connects distant quantum devices using quantum links in conjunction with conventional ones. Innovation that has made way for radically improved communications and computing skills. Regular computers use and analyse data in bits (0 or 1), whereas quantum computers use qubits, or quantum bits, which can simultaneously represent other states in addition to ones and zeros. This is how quantum computers vary from traditional computers. The majority of these methods for processing information on computers rely on symmetric or asymmetric cryptography algorithms. These encryption techniques can be vulnerable to attack. We analyse the quantum key distribution (QKD) technique with in a noise-free channel. In addition, we evaluate the QKD protocol with noisy channel to simulate real scenarios on the future Internet. Therefore, it would be essential to explore using quantum cryptography, which cannot be cracked by quantum computing, to secure the standard communications infrastructure used in cyber physical systems (CPS).
Keywords: Quantum computer; qubits; cryptography; cyber physical system